Measuring and Simulating Cellular Switching System IP Traffic. (March 2014) - Del Signore, Kenneth W.; Kam Ho, Tin; Jacquet, Phillipe
Abstract The increasing popularity of smartphones and other data‐enabled cellular devices has led to a rapid expansion of cellular data networks worldwide. These networks are constantly being improved to provide new functionality, improved capacity, and better reliability. Optimization, testing, and troubleshooting of these systems are all important areas of concern within the cellular network industry. Large amounts of engineering resources are devoted to these topics, with the result that analysis techniques and best practices are constantly being improved. This paper details recent work regarding the analysis of cellular data device behavior in a live system, and the design of a high performance load generator to simulate this behavior for use in system testing and debugging. Internet Protocol (IP) packet capture data is analyzed using a simple graph‐based analysis technique that provides a detailed characterization of device behavior. This characterization is then used in the design of a second generation high performance load generator. © 2014 Alcatel‐Lucent.